CLIMATE CHANGE, EMERGENCY SITUATIONS AND THE RESPONSE OF SERBIA, MONTENEGRO, AND CROATIA - Todić, Dragoljub C (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The aim of the paper is to examine the nature of the connections between climate change and emergency situations in legal systems of three states. The first part of the paper is devoted to the attitude of Serbia, Montenegro and Croatia towards climate change and emergency situations. The norms of laws regulating the field of climate change (from the point of view of potential relevance for emergency situations) and laws regulating the field of emergency situations (from the point of view of potential relevance for climate change) are analyzed. In the second part of the paper the question of the membership of Serbia, Montenegro and Croatia in the relevant international agreements is pointed out. The position is considered that the issue of the relationship between climate change and emergency situations is not regulated in a comprehensive way, and the connections between climate change and emergency situations are recognized inconsistently by internal regulations. In the conclusion, it is stated that the links between climate change and emergency situations are partially recognized in law and that there is room for a significantly clearer definition. The character of the links between climate change and emergency situations should be viewed in the light of the development of international law and the specifics of the legal systems of the three countries, including their status within the EU integration.